Microgrids: a decentralized alternative for rural electrification in Nigeria (2020)
Poor electricity services remain a major obstacle to growth in Nigeria, as inadequate and epileptic power supply undermines investment opportunity, economic growth, social and infrastructure developments. Centralized power generation, transmission and distribution system operations in Nigeria can no longer deliver competitively cheap and reliable electricity to remote customers on and off the national grid. Anticipated development in generation with a balanced combination of ongrid and off-grid power projects is very achievable in Nigeria. A balanced approach could potentially lead to an accelerated journey to full electrification in the country. This would in turn result in a significant boost of the country’s economy, as power has been proven to be an enabler of other sectors of the economy. This paper presents micro grids as a decentralized alternative for rural electrification in Nigeria. The paper reviews the electrification status in Nigeria, power management of micro grid and prospect of renewable energy for rural energy provision. The benefits, challenges and future prospects of micro grid are also discussed. Implementation of decentralized micro grid across 774 local governments of Nigeria with five (5) micro grids installed in each local government will not only improve the wellbeing of Nigerian rural dwellers, but also enhance Nigeria's energy and economic prospects for potential global investment.